Transaksi Ekonomi Klasik Masyarakat Aceh (Analisis Kelayakan Taqnin Hukum Ekonomi Syariah) - Fahriansah, Fahriansah (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2017)
Aceh is one of provinces in Indonesia (NKRI) granted special freedom to regulate households independently (formal juridical) in accordance with Islamic Shari'a. Islamic syariat covers about the economy. Economic activity in Aceh has special characteristics that are not against Islamic law, such as mawah, gala, and peublo aqad. Therefore, formal regulation is required to protect the business people and to safeguard Acehnese culture.